Development and Characterization of Lyophilized Chondroitin Sulfate-Loaded Solid Lipid Nanoparticles: Encapsulation Efficiency and Stability - Marta E. Bustos Araya; Anna Nardi Ricart; Ana C. Calpena Campmany; Rafel Prohens; Montserrat Miñarro Carmona (Pharmaceutics)
This study explores the development and characterization of lyophilized chondroitin sulfate (CHON)-loaded solid lipid nanoparticles (SLN) as an innovative platform for advanced drug delivery. Background/Objectives: Solid lipid nanoparticles are increasingly recognized for their biocompatibility, their ability to encapsulate diverse compounds, their capacity to enhance drug stability, their bioavailability, and their therapeutic efficacy. Methods: CHON, a naturally occurring glycosaminoglycan with anti-inflammatory and regenerative properties, was integrated into SLN formulations using the hot microemulsion technique. Two formulations (SLN-1 and SLN-2) were produced and optimized by evaluating critical physicochemical properties such as particle size, zeta potential, encapsulation efficiency (EE%), and stability. The lyophilization process, with the addition of various cryoprotectants, revealed trehalose to be the most effective agent in maintaining nanoparticle integrity and functional properties. Results: Morphological analyses using transmission electron microscopy (TEM) and atomic force microscopy (AFM) confirmed the dimensions of the nanoscales and their structural uniformity. Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) revealed minimal excipient interaction with CHON, ensuring formulation stability. Stability studies under different environmental conditions highlighted that SLN-2 is the most stable formulation, maintaining superior encapsulation efficiency (≥88%) and particle size consistency over time. Conclusions: These findings underscore the potential of CHON-loaded SLNs as promising candidates for targeted, sustained-release therapies in the treatment of inflammatory and degenerative diseases.